‘Feeling Hot’: Exploring the feasibility of nocturnal erection detection through penile temperature measurements - Hille J. Torenvlied; Evelien Trip; Wouter Olthuis; Loes I. Segerink; Rob C. M. Pelger; Jack J. H. Beck (BJUI Compass)
Abstract Objectives The observational ‘Feeling Hot’ study aims to evaluate the feasibility of employing overnight penile temperature measurements for the detection of nocturnal erections, thereby contributing to the advancement and modernization of a non‐invasive diagnostic system for erectile dysfunction. Subjects/Patients and Methods In this proof‐of‐concept study, 10 healthy men aged 20–25 were recruited, following the methodology outlined in the ‘Staying Hot’ study by Torenvlied et al. Participants underwent ambulatory overnight penile temperature measurements concurrent with RigiScan recordings. Key outcome measures included baseline and peak penile temperatures during RigiScan‐annotated nocturnal erections. Reference measurements of the thigh temperature were also taken to assess nocturnal temperature variations. Results Statistically significant penile temperature increases (p = 0.008, n = 9) were observed during nocturnal erections, with an average elevation of 1.47°C noted during the initial erections. This underscores the practical utility of penile temperature measurements in detecting erection onset. Challenges arose in accurately determining erection duration and subsequent erection onsets due to the persistence of elevated temperatures following initial erections, termed the ‘Staying Hot effect’. Reference thigh temperature measurements aided in addressing this challenge. Conclusion Examining overnight penile temperature alongside simultaneous RigiScan recordings has yielded valuable insights into the viability of using the temperature methodology for detecting nocturnal erections. The ‘Feeling Hot’ study findings demonstrate significant penile temperature elevation during nocturnal erections in healthy young men, highlighting the potential of integrating this measurement methodology into the design of a modernized tool for ambulatory erectile dysfunction diagnostics. Further development of an advanced sensor system to comprehensively assess erection duration and quality is essential for enhancing clinical applicability.